Experimental Study on Solar Cooling Tube Using Thermal/Vacuum Emptying Method - Huizhong Zhao; Haibin Liang; Wenzhe Sun; Guoqing Yu; Dan Cao; Jun Ji (Advances in Materials Science and Engineering)
A solar cooling tube using thermal/vacuum emptying method was experimentally studied in this paper. The coefficient of performance (COP) of the solar cooling tube was mostly affected by the vacuum degree of the system. In past research, the thermal vacuum method, using an electric oven and iodine-tungsten lamp to heat up the adsorbent bed and H2O vapor to expel the air from the solar cooling tube, was used to manufacture solar cooling tubes. This paper presents a novel thermal vacuum combined with vacuum pump method allowing an increased vacuum state for producing solar cooling tubes. The following conclusions are reached: the adsorbent bed temperature of solar cooling tube could reaches up to 233°C, and this temperature is sufficient to meet desorption demand; the refrigerator power of a single solar cooling tube varies from 1 W to 12 W; the total supply refrigerating capacity is about 287 kJ; and the COP of this solar cooling tube is about 0.215.